Language and Communication Impact of Hypertension: A Qualitative Study - Cecilia Amponsem-Boateng; Timothy Bonney Oppong; Weidong Zhang; Tanko Abdulai; Jonathan Boakye-Yiadom; Lianke Wang; Emmanuel Kumi Duodu Kyere (International Journal of Hypertension)
Background. Hypertension (HTN) is the second main source of outpatient morbidity in Ghana, and the understanding of a disease is necessary for its prevention and management. Language and communication are contributing factors to HTN in Ghana. No studies have been conducted to assess knowledge/awareness of HTN (in the context of its understanding) among students in Ghana. Following a local name for HTN in Ghana, researchers interviewed students through a focus group to assess their understanding/perception (meaning, cause, and prevention) of the disease. Available literature has concerned itself with clients’ knowledge of their condition (diagnosis) rather than their comprehension of the true nature of what HTN is. The objective of this study is to assess the knowledge/awareness of HTN in the context of its understanding of the meaning, perception, causes, and prevention of hypertension among students of Ghana’s Senior High School (Second Cycle). Semistructured interviews with the use of the theme lists were employed. Focus group conversations and interviews were held in the local Akan (Twi) language, which was later translated, interpreted, and analyzed. Overall, 25 second-cycle students participated. 60% were between 15 and 17 years, 24% were ≥18 years, and 16% were <15 years of age. Males were 44% and females were 56%. Students gave diverse perceptions of their knowledge of HTN. The local language’s translation of HTN has influenced and affected its meaning/understanding among some, thus affecting their perception of causes and prevention.